(3GdHQb GdeJCdb aj eMGSf Mdbs - (3eMeO Hf eUWai Hf MOGhjQOi Hf eQGO Hf EHQGgjes; (3GdHdGPQj , CMeO Hf jMji Hf LGHQ Hf OGhO,J (B279 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi ZQS OhGe GdJhMjO GeG HYO adeG GfbUeJ Yf YQi GdUhajI hGfTbJ ai YUf THGHi s
(3BNQgG (B:s
(3hcd dZjQi aGfeG gh HYOi LGA eSc NGJegG bdJ ajgG hDQNG s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B267 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B201s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B45 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN (B10) s
Keywords: (3GdJGQjNs